Development of Islamic values through Arabic poetry; contribution of Arabic literature websites - Ahmad H.Osman, Rahmah; Abdullah, Nasimah (IIUM Press, 2017)
Children’s Arabic Literature websites have reflected great contribution in the development of Islamic values through Arabic poetry. The selection of these sites was due to their comprehensive nature in presenting literary works for Arab children. This research can be applied to textual analysis and survey. The results showed the presence of an overwhelming trend of the website towards entertainment. As for the social, national, and educational trends, they all held almost the same status. The use of such sites may contribute to advancement of Islamic values in children, along the relatively few published poems that contain Islamic symbols. The study has contributed to the subsequent and current version of the corpus that may lead to some stimulating studies in the use of language, text classification, and ideological factors among children texts. It has been concluded that website plays an active role to create the Islamic values in children. The website proved to be beneficial for the children in enhancing Arabic poetry among them.